Induced lipid peroxidation in ram sperm: semen profile, DNA fragmentation and antioxidant status. Issue 4 (April 2016) - Hamilton, Thais Rose dos Santos; Castro, Letícia Signori de; Delgado, Juliana de Carvalho; de Assis, Patrícia Monken; Siqueira, Adriano Felipe Perez; Mendes, Camilla Mota; Goissis, Marcelo Demarchi; Muiño-Blanco, Teresa; Cebrián-Pérez, José Álvaro; Nichi, Marcílio; Visintin, José Antonio; D'Ávila Assumpção, Mayra Elena Ortiz
Abstract : Action of reactive oxygen species, protamination failures and apoptosis are considered the most important etiologies of sperm DNA fragmentation. This study evaluated the effects of induced lipid peroxidation susceptibility on native semen profile and identified the mechanisms involved in sperm DNA fragmentation and testicular antioxidant defense on Santa Ines ram sperm samples. Semen was collected from 12 adult rams ( Ovis aries ) performed weekly over a 9-week period. Sperm analysis (motility, mass motility, abnormalities, membrane and acrosome status, mitochondrial potential, DNA fragmentation, lipid peroxidation and intracellular free radicals production); protamine deficiency; PRM1, TNP1 and TNP2 gene expression; and determination of glutathione peroxidase (GPx), glutathione reductase, catalase (CAT) and superoxide dismutase activity and immunodetection in seminal plasma were performed. Samples were distributed into four groups according to the sperm susceptibility to lipid peroxidation after induction with ascorbate and ferrous sulfate (low, medium, high and very high). The results were analyzed by GLM test and post hoc least significant difference. We observed an increase in native GPx activity and CAT immunodetection in groups with high susceptibility to induced lipid peroxidation. We also found an increase in total sperm defects, acrosome and membrane damages in the group with the highest susceptibility to induced lipid peroxidation. Additionally, the low mitochondrial membrane potential, susceptible to chromatin fragmentation and the PRM1 mRNA were increased in the group showing higher susceptibility to lipid peroxidation. Ram sperm susceptibility to lipid peroxidation may compromise sperm quality and interfere with the oxidative homeostasis by oxidative stress, which may be the main cause of chromatin damage in ram sperm.